A Neglected English Economist: George Poulett Scrope - Opie, Redvers (Quarterly Journal of Economics, 1929)
I. Biographical. II. Method: the place of “natural principles,” 106; the importance of experience in generalising, 107; the significance of institutions and the rational control of them, 108. — III. Impetus from practical problems: population, 110; the poor laws, 112; public work, 113; mutual assurance, 114. His outlook in harmony with his social philosophy; its relation to laissez-faire, 115. — IV. Monetary and banking problems. Fluctuations in prices the main evil, 117; an advocate of paper currency and greater control over prices, 119; the need for a “tabular standard,” 121. Theory of crises, 123. — V. A critic of “orthodox” contemporaries, 126; modern analysis of demand and supply mechanism, 127; superior treatment of distribution, 129. — Bibliographical appendix, 134.